THE IMPORTANCE OF LIFE STRATEGIES IN THE FORMATION OF THE STUDENT’S PERSONALITY (World Bulletin of Education and Learning, 2025)
The article is devoted to the scientific-theoretical analysis of the definition of the concept “life strategy,” developed by modern researchers, and the essence of an individual’s life strategy.
Keywords: Life strategy, life goals, satisfaction with life, emotional intelligence, independence, issues in studying life strategies.